Central skull base osteomyelitis: a rare but life-threatening disease. Issue 4 (August 2015) - Orioli, L.; Boute, C.; Eloy, P.; De Wispelaere, J. -F.; De Coene, B.; Huang, T. D.; Ausselet, N.; Delaere, B.
Abstract : We present the case of a 70-year-old non-diabetic patient who presented to the emergency department with unrelenting otalgia. A severe otitis externa (OE) and mastoiditis were treated with broad spectrum antibiotics and surgical drainage. No bacteria was isolated from surgical samples. Because the otalgia persisted, a magnetic resonance (MR) was performed and showed an infiltrating process at the skull base. Biopsies failed to prove malignancy or granulomatosis. The patient's neurological state deteriorated. The suspicion of a skull base osteomyelitis (SBO) was raised and proven by CT-guided biopsies that grew Pseudomonas aeruginosa. Meropenem and ciprofloxacin, given for 8 weeks, lead to a fast clinical improvement and a full recovery. SBO is uncommon, often complicating severe OE. Pseudomonas aeruginosa is the main pathogen. Prompt diagnosis and adequate antibiotherapy are required to lower mortality and morbidity. The diagnosis may be delayed because of unawareness and large differential diagnosis including solid neoplasic tumours, malignant hemopathies and granulomatosis.